Presage criteria for blog credibility assessment using Rasch analysis / Sharifah Aliman, Saadiah Yahya and Syed Ahmad Aljunid - Aliman, Sharifah; Yahya, Saadiah; Aljunid, Syed Ahmad (CMIWS and UiTM Press, 2011)
Credibility is an entrance path to trust model environment and its impact is so tremendous to the blogosphere and real world. The natural unique of blogs features compared with ordinary websites, the rise of information propagation through blogs and the scarcity of blog credibility research have sparked the impetus to investigate blog credibility assessment. This paper presents an exploratory study to identify credibility factors used by local blog users in assessing blogs. Our survey respondents are from local university that consisting of academic staff and students who are computer and Internet literate. Data was analyzed using person-item distribution map (PIDM) Rasch analysis. The results indicated that 75% credibility criteria, which was validated using misfit item, are preferable for assessing blog credibility. However, only 46% credibility criteria, which was validated using person gap difference, are acceptable. It also shows that update blog content, reputation of blog authors as well as recognition and performance of blog site are inapt criteria to assess blog credibility. Inspite, most of our credibility criteria are fit to formulate our new blog credibility model. Our study also suggests that Rasch analysis is significantly worthy to validate criteria that most of previous researches employed descriptive statistics and factor analytic approach’.